Transparansi Partai Politik dalam Rekrutmen Calon Legislatif - Nendissa, Reny Heronia; Rahakbauw, Claudio Patrick I (SASI, 2020)
The development of democracy, the role and function of political lebih parties is more complete. This is due to the large expectations that are developing, so the function and role of the party will increase. However, the pattern of recruitment of candidates who do not consider the requirements to gain the votes of political parties. Based on the aforementioned background, the problem to be studied is the regulating the recruitment patterns of legislative candidates by political parties. The research method used in this discussion is normative juridical research using a research proposal-law (statute approach) and accessing concepts (conceptual approach). there is a legislative candidate who can be moved freely to another party and only joins when he will be nominated as a candidate by setting aside the old conditions as cadres approved by the party. Through this agreement, it was agreed that political parties could be emphasized by the principle of their parties to select candidates through clear and transparent recruitment patterns